Design and Performance Evaluation of a Multi-Temperature Flat Plate Solar Collector - Zwalnan, Selfa Johnson; Duvuna, Gideon Ayuba; Abakr, Yousif Abdalla; Banda, Tiyamike (International Journal of Renewable Energy Development, 2021)
The standard flat-plate solar collector utilises a single copper tube to remove the absorber plate’s heat. This type of collector’s primary purpose is to provide hot water for a single application. Hot water can be required for different applications at different temperatures. Besides, using the standard collector’s configuration may increase thermal demand and increase the collector’s size. Therefore, this study proposes a novel solar water heating configuration that uses three in-line fluid passages. The goal is to design a single collector that provides hot water for various uses: Sterilisation, washing, and postnatal care. Thus, the proposed system was modelled, and a numerical simulation conducted. This analysis compares the proposed system’s output and the standard collector’s output. The results showed that the thermal load demand was reduced by 27% when the hot water demand for these services was generated using three separate tanks. The serpentine collector’s efficiency with three fluid passages is increased by 20% compared to the traditional serpentine collector. The thermal energy delivered to meet load was 30% higher than that of the traditional serpentine system. The experimental and simulated system performance is in near agreement with an average percentage error Cv(RMSE) of 8.75% and confidence level NSE of about 87%. Since the proposed serpentine collector has a higher overall thermal production, it is recommended for use with hot water, which has to be heated to different temperatures.